EVALUATION OF PHYTOCHEMICALS, ANTIOXIDANT ACTIVITY AND NUTRIENT CONTENT OF CENTELLA ASIATICA (L.) URBAN LEAVES FROM DIFFERENT LOCALITIES OF ASSAM - SRISTISRI UPADHYAYA,; L. R. SAIKIA, (International Journal of Pharma and Bio Sciences, 2012)
Leaves of Centella asiatica collected from three districts (considered different samples) of Assam were analysed for phytochemical constituents, antioxidant activity and nutrient content. Data showed that saponin, tannin, phenol, flavonoid, trapezoid, cardiac glycoside, alkaloid and reducing sugar were present in all the samples. The order of total phenolic content and antioxidant activity of the samples were sample 2 > sample 3 > sample 1 while the order of nutrient content was sample 1> sample 3> sample 2. The results revealed that both primary and secondary metabolite content of plants varies with variation of growing localities.